Promosi Kesehatan Kader Posyandu Melati 6 dalam Pelaksanaan Pekan Imunisasi Nasional (PIN) di Desa Lengkong Kulon Pagedangan, Kabupaten Tangerang-Banten. - Ade Siti Khaeriah (Lembaga Pengembangan Kinerja Dosen, 2024)
Pekan Imunisasi Nasional or The Polio Immunization Week (PIN) program is an important government initiative to eliminate polio in Indonesia. Posyandu cadres play a key role in the implementation of this program, especially in terms of health promotion and increasing immunization coverage. In Lengkong Kulon Village, Pagedangan Sub-district, Tangerang Regency-Banten, health promotion efforts are also carried out by Posyandu Melati 6 cadres to invite the community to participate in the Polio PIN held on 27 May and 16 August 2024, so as to achieve optimal immunization coverage targets. This study used a qualitative descriptive approach. Data were collected through observation and in-depth interviews with Posyandu Melati 6 cadres, community members and local health officials. Observation and analysis of related documents were also conducted to complement the information obtained. The findings show that Posyandu Melati 6 cadres in Lengkong Kulon village have been active in disseminating information about the importance of polio immunization and organizing health education activities. However, there were some challenges, including limited resources, lack of training, and communication barriers with the community. Nonetheless, the proactive involvement of Posyandu cadres and support from village officials, community leaders, village midwives, and the surrounding community, contributed to the increase in immunization coverage.